A stable rhodium single-site catalyst encapsulated within dendritic mesoporous nanochannels. Issue 3 (21st December 2017) - Tian, Jun; Yang, Dali; Wen, Jianguo; Filatov, Alexander S.; Liu, Yuzi; Lei, Aiwen; Lin, Xiao-Min
Abstract : A stable single-site Rh catalyst was formed inside individual channels of three-dimensional dendritic mesoporous silica nanospheres through aminosilane binding. The catalyst demonstrated an excellent activity, stability and recyclability in the reduction of 4-nitrophenol, high regioselectivity in the hydrosilylation of terminal alkyne. Abstract : Catalysis plays an essential role in the modern chemical industry. However, it still remains a great challenge to improve the efficiency of many heterogeneous catalysts based on a per metal atom basis. Single-site catalysts (SsCs) with isolated metal atoms/ions anchored to the supports are thus highly desirable, providing an innovative solution towards highly efficient usage of precious metal atoms in heterogeneous catalysts. Creating SsCs with high metal loading proves to be challenging because, without robust anchoring, atoms tend to diffuse to form large aggregates during catalytic reactions. We report a facile ligand exchange method to anchor a single-site Rh catalyst inside the individual channels of three-dimensional dendritic mesoporous silica nanospheres (MSNSs). The short porous channels inside MSNSs provide an easy access of reactants and the strong binding of the ligand prevents the aggregation of catalyst sites. The as-synthesized Rh1 @MSNS-NH2 catalyst shows excellent activity, stability and reusability in the reduction of 4-nitrophenol. The same catalyst shows high regioselectivity in the hydrosilylation of terminal alkynes to yield α-vinylsilanes through the Markovnikov addition.